Vindkraft på skogsmark: Privata skogsägares syn på bevarande av biologisk mångfald vid vindkraftsetablering - Tomasdotter,Villemo (2025)
This study aimed to gain a deeper understanding of Swedish small forest owners’ perspectives on ecological compensation on their land in relation to wind farm construction, specifically how their sense of ownership influences their willingness to engage in such activities. To fulfil this aim, semi-structured interviews were conducted with ten private forest owners who had signed agreements for wind power development with the renewable energy company Eolus AB. A three-dimensional ana-lytical framework was applied to analyse the empirical material from an ownership perspective. The results show that most of the interviewed forest owners are negative toward ecological compensation. However, respondents with higher education in forestry or related subjects were more positive. Using the analytical framework, key influencing themes emerged that could explain the forest owner’s reluctance to ecological compensation, such as economic considerations, a sense of responsibility to address climate change, identification with production forestry, and the im-portance of retaining decision-making power over their land. A long-standing family connection to the forest also shaped their views regarding land use in their forest. While many forest owners viewed ecological compensation as conflicting with their produc-tion-oriented identity, several opportunities were identified. These include establishing guarantees for compensation efforts, offering economic incentives for lost production, and building on existing relationships between forest owners and wind power developers. Such approaches may help foster legitimacy, strengthen empowerment, and support the creation of new forest values. If implemented thoughtfully, these strategies could enhance collaboration with private forest owners and contribute positively to biodiversity conservation in Sweden
Keywords: Wind power; biodiversity; offsetting